Quality optical measurement system for shiny jet engine turbine vanes - Bai, Songlin (2008)
Our main objective is to develop a measurement algorithm and software to process the laser sensor measurement data of jet engine turbine vane surfaces, and to reconstruct 3D profiles of these surfaces. In particular, the corrupted data due to the specular reflection are processed to obtain a nominal 3D surface profile.